Tahap Kesedaran Pelajar Terhadap Kepentingan Media Sosial Dalam Keusahawanan - Rosland Buja (LP2M Politeknik Jambi, 2023)
Many entrepreneurs today need to change their business and service platforms in line with the current era of social media development to keep up with the changes in modern style by using social media as the main channel for marketing, sales and advertising. Due to these changes, entrepreneurs also need to adapt and gain a competitive advantage in today's highly competitive business environment. However, not all entrepreneurs or even community understand the importance of social media. Therefore, the purpose of this study is to evaluate the level of public awareness in importance of social media in entrepreneurship field. The respondents were 136 students from Politeknik Kuching Sarawak. Data were obtained from questionnaires that were randomly distributed online and analysis was conducted using SPSS software. The results of the analysis survey conducted shows that the majority of students understand the importance of social media for entrepreneurs. The implications of this study show the need for training and programs related to digital entrepreneurship. Those who understand the importance of digital gadget applications will be more easily apply and using it in any activity including the field of entrepreneurship